2006
DOI: 10.1007/s11426-005-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalyzed asymmetric Pauson-Khand reaction using SDP ligands

Abstract: The activity and enantiocontrol ability of the chiral catalysts prepared from spiro diphosphine ligands, SDP, and rhodium precursor were investigated in the asymmetric catalytic Pauson-Khand reaction. The results showed that SDP ligands were very effective in Rh-catalyzed Pauson-Khand reaction, and their complexes with rhodium could convert a variety of 1,6-enyne compounds into bicyclopentone derivatives under CO atmosphere in high yields with good enantioselectivities. The SbF 6 − was found to be a suitable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The transformation is well-known as both intermolecular and intramolecular versions, the latter being more widely exploited after its introduction in the early 1980s. 187 Several metal carbonyls have been applied as carbon monoxide source instead of dicobalt octacarbonyl, such as molybdenum, [188][189][190][191][192][193][194] titanium, [195][196][197][198][199][200][201][202][203] zirconium, 197,204,205 ferrium, 206 nickel, 207,208 iridium, [209][210][211][212] rhodium, [213][214][215][216][217][218][219][220] and ruthenium 213,[221][222][223][224] carbonyls. More recently, it has been found that PdCl 2 coordinated to a thiourea ligand could also catalyze an intramolecular reaction.…”
Section: Pauson-khand Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation is well-known as both intermolecular and intramolecular versions, the latter being more widely exploited after its introduction in the early 1980s. 187 Several metal carbonyls have been applied as carbon monoxide source instead of dicobalt octacarbonyl, such as molybdenum, [188][189][190][191][192][193][194] titanium, [195][196][197][198][199][200][201][202][203] zirconium, 197,204,205 ferrium, 206 nickel, 207,208 iridium, [209][210][211][212] rhodium, [213][214][215][216][217][218][219][220] and ruthenium 213,[221][222][223][224] carbonyls. More recently, it has been found that PdCl 2 coordinated to a thiourea ligand could also catalyze an intramolecular reaction.…”
Section: Pauson-khand Reactionmentioning
confidence: 99%
“…The transformation is well-known as both intermolecular and intramolecular versions, the latter being more widely exploited after its introduction in the early 1980s . Several metal carbonyls have been applied as carbon monoxide source instead of dicobalt octacarbonyl, such as molybdenum, titanium, zirconium, ,, ferrium, nickel, , iridium, rhodium, and ruthenium , carbonyls. More recently, it has been found that PdCl 2 coordinated to a thiourea ligand could also catalyze an intramolecular reaction. The classical version of PKR involved a stoichiometric quantity of cobalt carbonyl, while the recent catalytic variants require substoichiometric amounts of cobalt or other transition metals.…”
Section: Pauson−khand Reactionmentioning
confidence: 99%
“…Due to their structural rigidity and stability, chiral spiro diphosphine ligands have witnessed great advances . In 2003, Zhou and co-workers reported the design and synthesis of a novel spiro diphosphine ligand, termed as SDP, which has been widely utilized in asymmetric catalysis . In 2012, another novel spiro diphosphine ligand SKP was developed by Ding and co-workers (Figure ).…”
mentioning
confidence: 99%
“…Alternatively, asymmetric PKRs with other metal catalysts have been explored . Up to date, Rh catalysts have proved to be promising for asymmetric PKRs because of their electrical properties (Scheme B). Unfortunately, the application of this strategy remains greatly limited by the narrow substrate scope. For example, to the best of our knowledge, only terminal alkenes and allenes were reported in the Rh-catalyzed asymmetric PKRs.…”
mentioning
confidence: 99%